2008
DOI: 10.1248/bpb.31.149
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Gallic Acid from Sanguisorbae Radix on Amyloid .BETA. Protein (25-35)-Induced Toxicity in Cultured Rat Cortical Neurons

Abstract: ] c , and then by inhibiting glutamate release and generation of ROS, and that these effects of gallic acid may be partly associated with the neuroprotective effect of Sanguisorbae radix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…Gallic acid and vanillic acid showed neuroprotective effect, AchE inhibitory activity and antioxidant effect (Ban et al ., 2008; Ghayur et al ., 2011; Gan et al ., 2011; Weon et al ., 2012). Ferulic acid was also protected against memory and learning deficit induced β-amyloid peptide in mice and had antioxidant activity (Cho et al ; 2005).…”
Section: Disscusionmentioning
confidence: 99%
“…Gallic acid and vanillic acid showed neuroprotective effect, AchE inhibitory activity and antioxidant effect (Ban et al ., 2008; Ghayur et al ., 2011; Gan et al ., 2011; Weon et al ., 2012). Ferulic acid was also protected against memory and learning deficit induced β-amyloid peptide in mice and had antioxidant activity (Cho et al ; 2005).…”
Section: Disscusionmentioning
confidence: 99%
“…36) Gallic acid, which is a main antioxidant in the acorn extract, 15) has been reported to inhibit Aβ(25-35)-induced [Ca 2+ ] i increases in rat cortical neurons. 21) In addition, octyl gallate reportedly inhibits Ca 2+ signaling in PC 12 cells through multiple pathways including voltage-gated Ca 2+ channel and Ca 2+ -permeable-ligand-ion channels. 37) Contents of phenolic compounds and gallic acid in the acorn extract used in this study were 5.43% 22) and 0.27%, 23) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17) Gallic acid has prevented Aβ(25-35)-induced apoptotic neuronal death by interfering with [Ca 2+ ] i increases in rat cortical neurons. 21) Massive release of glutamate induces [Ca 2+ ] i increases after acute brain injuries such as epilepsy and brain ischemia, which initiate many cellular processes including RoS formation. All these results suggest the possibility that acorn extract can be used as a supplement against glutamate excitotoxicity-related neurologic disorders including epilepsy and ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GA induced apoptosis in human leukemia HL-60RG cells (9), human lung cancer cell lines (10), human stomach cancer KATO III, colon adenocarcinoma COLO 205 cell line (11) and PC12 rat pheochromocytoma cells (12). It was also reported that GA plays an important role in the prevention of malignant transformation (13) and GA prevents amyloid ß-induced apoptotic neuronal death by interfering with the increase of Ca 2+ levels and then by inhibiting glutamate release and generation of ROS (14). GA was shown to have antitumor effects on LL-2 lung cancer cells transplanted in mice (15) and NCI-H460 human lung cancer cells in vitro and in vivo (10).…”
Section: Introductionmentioning
confidence: 94%